Modelling the pathogenesis of Myotonic Dystrophy type 1 cardiac phenotype through human iPSC-derived cardiomyocytes. (May 2018) - Spitalieri, Paola; Talarico, Rosa V.; Caioli, Silvia; Murdocca, Michela; Serafino, Annalucia; Girasole, Marco; Dinarelli, Simone; Longo, Giovanni; Pucci, Sabina; Botta, Annalisa; Novelli, Giuseppe; Zona, Cristina; et al.
Abstract: Myotonic Dystrophy type 1 (DM1) is a multisystemic disease, autosomal dominant, caused by a CTG repeat expansion in DMPK gene. We assessed the appropriateness of patient-specific induced pluripotent stem cell-derived cardiomyocytes (CMs) as a model to recapitulate some aspects of the pathogenetic mechanism involving cardiac manifestations in DM1 patients. Once obtained in vitro, CMs have been characterized for their morphology and their functionality. CMs DM1 show intranuclear foci and transcript markers abnormally spliced respect to WT ones, as well as several irregularities in nuclear morphology, probably caused by an unbalanced lamin A/C ratio. Electrophysiological characterization evidences an abnormal profile only in CMs DM1 such that the administration of antiarrythmic drugs to these cells highlights even more the functional defect linked to the disease. Finally, Atomic Force Measurements reveal differences in the biomechanical behaviour of CMs DM1, in terms of frequencies and synchronicity of the beats. Altogether the complex phenotype described in this work, strongly reproduces some aspects of the human DM1 cardiac phenotype. Therefore, the present study provides an in vitro model suggesting novel insights into the mechanisms leading to the development of arrhythmogenesis and dilatative cardiomyopathy to consider when approaching to DM1 patients, especially for the risk assessment of sudden cardiac death (SCD). These data could be also useful in identifying novel biomarkers effective in clinical settings and patient-tailored therapies. Graphical abstract: Highlights: Altered electrophysiological profile in ventricular-like CMs from Myotonic Dystrophy type 1 patients Down regulation of cardiac ion channel gene transcription in CMs from Myotonic Dystrophy type 1 patients compared to WT ones Instability of the beating period with a diminution of the beating force in CMs from Myotonic Dystrophy type 1 patients